Association between serum calcium level and the risk of acute kidney injury in ICU patients with subarachnoid hemorrhage: a retrospective cohort study - Zhao, Zhenlin; Xiao, Kuntai; Zhao, Sirong; Liu, Kangfeng; Huang, Fu; Xiao, Hua (Frontiers in Neurology, 2024)
Aim: To evaluate the association of serum calcium level with the risk of acute kidney injury (AKI) in patients with subarachnoid hemorrhage (SAH).: This retrospective cohort study extracted data of adults from the Medical Information Mart for Intensive Care (MIMIC-III, and MIMIC-IV) databases from 2008 to 2019. In the Logistic regression models, confounding variables including age, WBC, SBP, heart rate, BUN, glucose, INR, and CCI were finally adjusted by step-based regression. The outcome event was the occurrence of AKI after ICU admission.Univariate and multivariate Logistic regression models were utilized to assess the association of serum calcium level with the risk of AKI in SAH patients, with odds ratios (ORs) with 95% confidence intervals (CIs). To further explore the association, subgroup analyses stratified by age, Glasgow coma scale (GCS), drugs, and surgical methods.Results: A total of 1,128 patients with SAH, of which 457 patients developed AKI.Low levels of serum calcium were significantly associated with a high risk of AKI in patients with SAH, carried OR (95%CI) of 1.38 (1.01-1.89). Further subgroup analyses showed that low level of calcium was significantly associated with a high risk of AKI in SAH patients aged ≥60 years (OR=0.27, 95%CI: 0.09-0.83), who had GCS ≥13 (OR=1.57, 95%CI: 1.08-2.30), who did not use calcium channel blockers (CCB) (OR=2.22, 95%CI: 1.16-4.25) and angiotensin converting enzyme (ACE) inhibitors (OR=1.51, 95%CI: 1.06-2.14), and who did not undergo aneurysm embolization (OR=1.48, 95%CI: 1.01-2.17) and aneurysm clipping (OR=1.45, 95%CI: 1.04-2.01). Serum calcium level with the risk of AKI in patients with SAH 3 Conclusion: The results of our study indicated that low levels of serum calcium were 40 significantly associated with the risk of AKI in patients with SAH.